Assessing the Growth, Nodulation and Nitrogen Fixing Potential of Some Multipurpose Trees and Shrubs - Boakye, Y. E. (University of Ghana, 2001)
This study was conducted to assess the growth, nodulation and nitrogen fixing potential of some native multipurpose trees and shrubs. A total of fourteen species of indigenous leguminous trees and shrubs were initially screened for nodulation in three Ghanaian soils (Toje, Hatso and Alajo soil series), after 8 weeks of growth in nursery bags. The experiment was repeated with nine species of the tree/shrub legumes, this time under two levels of phosphorus (0 and 60 mg P/kg soil). The final study involved four of the tree/shrub legume species, which were assessed for both inoculation and phosphorus responses, and abilities to fix nitrogen as assessed by the 15N Isotope dilution method. Nodulation of the tree/shrub legumes by native rhizobia was highly variable, with five of the tree/shrub species, namely, Albizia lebbek, Sesbania aculiata, Pithecelobium spp, Tephrosia spp and Acacia farresiana being nodulated by native rhizobia in all three soils. In contrast, the following six tree legumes, Acacia adianthifolia, Albizia zygia, Acacia mangium, Senna occidentalis, Cassia occidentalis and Tamarindus indica did not form any nodule in any of the three soils. The presence of indigenous Rhizobium in all three soils, capable of nodulating A. lebbek, Pithecelobium spp, and Tephrosia spp was confirmed in a final study with four leguminous trees and shrubs; unioculated Leucaena spp however nodulated only in Toje soil. The number of rhizobia counted by the most probable number (MPN) method for the four legumes in the three soils ranged from 31/g soil to 1700/g soil. The populations of native Rhizobium/g soil capable of nodulating each of these four legumes were found to be highest in Alajo soil (mean 9.95 xlO2) while the least Rhizobium counts occurred in Hatso soil (mean 1.10 xlO2). Rhizobium isolates obtained from Tephrosia spp were found to be most promiscuous, and except for Leucaena spp, isolates from Tephrosia spp nodulated the two other tree species (i. e. A. lebbek,and Pithecelobium spp ), in contrast to isolates from A. lebbek and Pithecelobium spp which were found to be specific only for their respective host plants. Phosphorus application alone resulted in significantly improved nodulation (on average about 63%). Sesbania specioca, S. Aculiata and A. farresiana did not nodulate with the indigenous rhizobia without phosphorus in Toje soil but did nodulate after phosphorus application. Similarly, S. rostrata and Leucaena spp nodulated in Hatso and Alajo soils, only after phosphorus application. Despite the general response by the trees to phosphorus, some species, like A. lebbek, S. aculiata and Tephrosia spp did not respond significantly to phosphorus application on Alajo soil. Phosphorus application, however did not result in significant increase in both %N fixed (about 38%) and total N (about 44 mg) fixed. Also, with the exception of Tephrosia spp, P application did not result in significant increase in total dry matter yield of the tree legumes. Although inoculation resulted in more than double nodule numbers of the tree species, it did not result in significant increase in both total N fixed and %N fixed. It also did not significantly increase total dry matter yield except in the case of Tephrosia spp. Leucaena responded highest to inoculation with an increase of over 123% total N fixed. In general however, Tephrosia spp gave the highest Biological Nitrogen Fixation (BNF) followed by Pithecelobium spp and A. lebbek with the lowest being Leucaena in terms of both percent and total N fixed. These studies therefore identified Tephrosia spp as having high potential for both dry matter yield and nitrogen fixation. Because of the high numbers of native rhizobia present in the soils studied, Tephrosia spp stands a good chance of being used for nitrogen recycling.
Thesis(MPhil.)-University of Ghana, 2001